2017
DOI: 10.1038/icb.2016.122
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydial protease‐like activity factor mediated protection against C. trachomatis in guinea pigs

Abstract: We have comprehensively demonstrated using the mouse model that intranasal immunization with recombinant chlamydial protease-like activity factor (rCPAF) leads to a significant reduction in bacterial burden, genital tract pathology and preserves fertility following intravaginal genital chlamydial challenge. In the present report, we evaluated the protective efficacy of rCPAF immunization in guinea pigs, a second animal model for genital chlamydial infection. Using a vaccination strategy similar to the mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…caviae from the infected conjunctivae of young laboratory guinea pigs and defined it as the causative agent of guinea pig inclusion conjunctivitis [ 11 ]. The infection of guinea pigs with human Ct serovars D and E [ 12 ], and the usage of this model for Ct vaccination studies [ 13 ], was described in the genital, but not in the ocular, animal model. The major disadvantage of the ocular guinea pig model has been the lack of a wide range of immunological reagents/consumables, knockout animals, and easily accessible inbred guinea pig strains.…”
Section: Introductionmentioning
confidence: 99%
“…caviae from the infected conjunctivae of young laboratory guinea pigs and defined it as the causative agent of guinea pig inclusion conjunctivitis [ 11 ]. The infection of guinea pigs with human Ct serovars D and E [ 12 ], and the usage of this model for Ct vaccination studies [ 13 ], was described in the genital, but not in the ocular, animal model. The major disadvantage of the ocular guinea pig model has been the lack of a wide range of immunological reagents/consumables, knockout animals, and easily accessible inbred guinea pig strains.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][21][22][23][24][25][26][27][28] We also have shown that rCPAF + IL-12 vaccination protects against C. muridaruminduced disease sequelae in the female mouse upper reproductive tract including hydrosalpinx formation and infertility. 3,4,27,28 However, these disease sequelae were not induced by C. trachomatis infection in mice or guinea pigs and therefore we have not been able to confirm the efficacy of the vaccine against the human pathogen. In this context, we noted that CPAF is a highly conserved chlamydial protein, and a strong association between C. pneumoniae and exacerbation of atherosclerosis in human individuals, and a cause-and-effect relationship in mice and rabbits has been demonstrated.…”
Section: Discussionmentioning
confidence: 78%
“…We have shown previously that immunization with rCPAF cloned from C. trachomatis serovar L2 genome, with IL-12 or CpG-ODN as adjuvant, can enhance clearance of C. muridarum and C. trachomatis infection in mice and guinea pigs, respectively 2-4, 21-28 . We also have shown that rCPAF+IL-12 vaccination protects against C. muridarum -induced disease sequelae in the female mouse upper reproductive tract including hydrosalpinx formation and infertility 3, 4, 27, 28 . However, these disease sequelae were not induced by C. trachomatis infection in mice or guinea pigs and therefore we have not been able to confirm the efficacy of the vaccine against the human pathogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ct-secreted serine protease or Chlamydia protease-like activity factor (CPAF) [74,75] is a dimeric complex [76,77] and an immunodominant antigen [78], which has been shown to promote Ct survival in the mouse lower genital tract [79], potentially via targeting host innate effectors [80,81]. Immunization with a recombinant CPAF alone, or in combination with other antigens, induced significant protection against infection and pathology in various mouse strains and guinea pigs [82][83][84][85]. The chlamydial major outer membrane protein (MOMP) is the serovar-typing antigen with multiple B and T cell epitopes [86][87][88] and has long been proposed as a vaccine candidate [89][90][91].…”
Section: Subunit Vaccinesmentioning
confidence: 99%